Strategic Management of the Financial System in the Conditions of Economy Globalization - BEREZYUK, Valentina; DARIBEKOVA, Nazgul; DARIBEKOVA, Aigul; MELNIK, Margarita; GORDOVA, Marina (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).40, 2018)
Strategic management of the financial system of the Republic of Kazakhstan in the context of the globalization of the economy is one of the main conditions and factors for ensuring financial stability in the country. The implementation of supervisory powers in the financial sphere is carried out in each country in the institutional forms established by law. The choice of a specific method of regulating organization is determined by the set of factors characteristic for each country. The forms of implementation of regulatory functions in each particular country do not remain unchanged, they are constantly being improved. The creation of a separate regulatory body to oversee all participants of the financial market in the Republic of Kazakhstan is an important step in the development of the regulation of the financial system of the Republic of Kazakhstan. World practice shows that such a regulatory framework is most effective for the development of the financial sector, financial instruments and financial intermediation services